2020
DOI: 10.1002/mco2.46
|View full text |Cite
|
Sign up to set email alerts
|

Pathway‐extended gene expression signatures integrate novel biomarkers that improve predictions of patient responses to kinase inhibitors

Abstract: Cancer chemotherapy responses have been related to multiple pharmacogenetic biomarkers, often for the same drug. This study utilizes machine learning to derive multi‐gene expression signatures that predict individual patient responses to specific tyrosine kinase inhibitors, including erlotinib, gefitinib, sorafenib, sunitinib, lapatinib and imatinib. Support vector machine (SVM) learning was used to train mathematical models that distinguished sensitivity from resistance to these drugs using a novel systems bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 94 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…Both FSFS and BSFS models were derived from the top 50 ranked mRMR genes, in addition to other published radiation responsive genes: AEN, BAX, BCL2, DDB2, FDXR, PCNA, POU2AF1, and WNT3. SVMs were derived with a Gaussian radial basis function kernel by iterating over box-constraint (C) and kernel-scale (σ) parameters and gene features, minimizing to either misclassification or log loss by cross-validation (Zhao et al 2018a;Bagchee-Clark et al 2020). Gene signatures were then assessed with a validation dataset and re-evaluated (by misclassification rates, log loss, Matthews correlation coefficient, or goodness of fit).…”
Section: Derivation Of Radiation Gene Signaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both FSFS and BSFS models were derived from the top 50 ranked mRMR genes, in addition to other published radiation responsive genes: AEN, BAX, BCL2, DDB2, FDXR, PCNA, POU2AF1, and WNT3. SVMs were derived with a Gaussian radial basis function kernel by iterating over box-constraint (C) and kernel-scale (σ) parameters and gene features, minimizing to either misclassification or log loss by cross-validation (Zhao et al 2018a;Bagchee-Clark et al 2020). Gene signatures were then assessed with a validation dataset and re-evaluated (by misclassification rates, log loss, Matthews correlation coefficient, or goodness of fit).…”
Section: Derivation Of Radiation Gene Signaturesmentioning
confidence: 99%
“…Our approach uses supervised machine learning (ML) with genes previously implicated or established from genetic evidence and biochemical pathways that are altered in response to these exposures (Zhao et al 2018a). Biochemically-inspired ML is a robust approach to derive diagnostic gene signatures for radiation and chemotherapy (Dorman et al 2016;Mucaki et al 2016;Mucaki et al 2019;Bagchee-Clark et al 2020). Given the limited sample sizes of typical datasets, appropriate ML methods for deriving gene signatures have included Support Vector Machines, Random Forest classifiers, Decision Trees, Simulated Annealing, and Artificial Neural Networks (Rogan, 2019;Boldrini et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning has many advantages in analyzing datasets with large samples and features compared with traditional biostatistical methods, which makes it deployable to build prediction models for survival and treatment efficacy in cancer patients ( 19 , 20 ). LASSO and Cox regression analyses are commonly employed as machine learning methods to develop risk models ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both genomic complexity-and physiology-based approaches are necessary to understand the relationship between genotypes and phenotypes. Finally, Bagchee-Clark et al (2020) have shown that machine learning-based, pathway-extended gene expressions measurements can be successfully used to identify novel biomarkers that improve predictions of patient response to drugs in cancer therapy.…”
Section: Pathway-based Approaches Would Provide a Handle On Network Complexitymentioning
confidence: 99%